2009
DOI: 10.1785/0120080205
|View full text |Cite
|
Sign up to set email alerts
|

Review: Progress in Rotational Ground-Motion Observations from Explosions and Local Earthquakes in Taiwan

Abstract: Rotational motions generated by large earthquakes in the far field have been successfully measured, and observations agree well with the classical elasticity theory. However, recent rotational measurements in the near field of earthquakes in Japan and in Taiwan indicate that rotational ground motions are 10 to 100 times larger than expected from the classical elasticity theory. The near-field strong-motion records of the 1999 M w 7:6 Chi-Chi, Taiwan, earthquake suggest that the ground motions along the 100 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…However, our data set is small and we will need far more data to establish any significant relationship. Nevertheless, Lee et al (2009) performed a data fitting to these data and to the data presented by Takeo (2009), and they discussed this linear relationship.…”
Section: Data Obtained During the Phase 2 Operationmentioning
confidence: 99%
“…However, our data set is small and we will need far more data to establish any significant relationship. Nevertheless, Lee et al (2009) performed a data fitting to these data and to the data presented by Takeo (2009), and they discussed this linear relationship.…”
Section: Data Obtained During the Phase 2 Operationmentioning
confidence: 99%
“…Lee et al (2009b) already showed the difference in the slope between the Takeo (2009) and Liu et al (2009) datasets. We suggest that this can be explained by an effect of the magnitude on the rotations.…”
Section: "Peak Value" Analysis Of the Datasetsmentioning
confidence: 96%
“…Despite the above reservations, installed R-1 rotational seismometers have for instance recorded several hundred local earthquakes and two explosions in Taiwan [74]. The largest peak rotational rate recorded at the HGSD station (up to early 2008) was from an earthquake with magnitude 5.1 at 13:40 UTC 23 July 2007.…”
Section: Rotational Seismometers For Direct Measurement Of Rotationmentioning
confidence: 99%